(untitled) (Research, Society and Development, 2021)
Popcorn consumption is increasing progressively worldwide. Landrace popcorn (LP) are cultivated in family farming. The objective of this study was to characterize a LP in an organic system by family farmers. LP was analysed for the phenotypic characterization and race identification, germination and vigor, thickness/width ratio, circularity index, sphericity, diameter ratio, geometric mean diameter, volume, surface area, angle of repose (AR), hectoliter weight (HW), apparent specific gravity (ASG), thousand kernel weight (TKW), color, and classification according to identity and quality requirements. LP is of an indigenous Guarani origin and belongs to the Avatí Pichingá Ihú race. The variety yields a high germination and vigor and can be used as seeds. The dimensions and calculated indices had important variations among the grains, demonstrating a wide genetic diversity, typical of landraces. The low AR, associated with the dimensions, revealed the small size of the LP grains. Higher values for HW, ASG, and TKW indicated higher levels of vitreous endosperm, hardness, and starch content. The coordinates a * and b * respectively indicate the red and yellow colors while the low value for the parameter L * indicates the intense color of the LP. Corn was classified as type 1 according to the percentage of physical defects, however, the expansion capacity presented a value below the reference for commercialization. The potential of the studied variety is verified to be used by industries, mainly the food sector. Its cultivation can be stimulated by family farming, ultimately impacting grain production and promoting the rescue of germplasm.